Exploring the Personal Recovery Construct in Bipolar Disorders: Definition, Usage and Measurement. A Systematic Review - Chirio-Espitalier, Marion; Schreck, Benoit; Duval, Melanie; Hardouin, Jean-Benoit; Moret, Leila; Bronnec, Marie Grall (Frontiers in Psychiatry, 2022)
Personal recovery from psychiatric disorders is a journey towards a satisfying and hopeful life despite the possible persistence of symptoms. This concept has gained interest and become an increasingly important goal in mental health care programmes. Personal Recovery is well described in the context of severe mental illnesses in general, but little is known about this journey in bipolar disorders and the factors underlying it. A systematic review was conducted according to the PRISMA recommendations, focusing on studies exploring personal recovery in bipolar disorder specifically. The latter have integrated a comprehensive approach to the concept, the existing means of measurement or have explored the levers of recovery in care. Twenty-four articles were selected, including 7 qualitative, 12 observational, and 5 interventional studies. The Bipolar Recovery Questionnaire was the only scale developed de novo from qualitative work with bipolar people. Personal recovery did not correlate very closely with symptomatology. Some elements of personal recovery in bipolar disorder were similar to those in other severe mental illnesses: meaning in life, self-determination, hope, and low self-stigma. Specific levers differed: mental relationships with mood swings, including acceptance and decrease in hypervigilance, and openness to others, including trust and closeness. The studies highlighted the role of caregiver posture and the quality of communication within care, as well as the knowledge gained from peers. The choice to exclude articles not focused on bipolar disorder resulted in the provision of very specific information, and the small number of articles to date may limit the scope of the evidence. New components of personal recovery in bipolar disorder emerged from this review; these components could be taken into account in the construction of care tools, as well as in the caregiving posture. Strengthening skills of openness to others could also be a central target of recovery-focused care.